Mobile Phones in the Bedroom: Trajectories of Sleep Habits and Subsequent Adolescent Psychosocial Development - Vernon, Lynette; Modecki, K.; Barber, B. (Wiley-Blackwell Publishing Ltd, 2018)
© 2017 The Authors. Child Development © 2017 Society for Research in Child Development, Inc. Mobile phones are an essential part of an adolescent's life, leading them to text, phone, or message into the night. Longitudinal latent growth models were used to examine relations between changes in adolescent night-time mobile phone use, changes in sleep behavior, and changes in well-being (depressed mood, externalizing behavior, self-esteem, and coping) for 1,101 students (43% male) between 13 and 16 years old. Both night-time mobile phone use and poor sleep behavior underwent positive linear growth over time. Increased night-time mobile phone use was directly associated with increased externalizing behavior and decreased self-esteem and coping. Changes in sleep behavior mediated the relation between early changes in night-time mobile phone use and later increases in depressed mood and externalizing behavior and later declines in self-esteem and coping.